Successful treatment of persistent aortoesophageal fistula after thoracic endovascular aortic repair (TEVAR) with esophageal bypass surgery: a case report - Chakrabandhu, Bandhuphat; Taksaudom, Noppon; Limpakan, Sirikan (Biomedical Sciences and Clinical Medicine, 2024)
This study reported a case of persistent aortoesophageal fistula after successful thoracic intravascular aneurysmorrhaphy. An esophageal bypass operation by gastric pull up procedure was performed in this case with a successful outcome.